Total Mercury (THg) Concentration in Indian Scad (Decapterus russelli) and Torpedo Scad (Megalaspis cordyla) from Southern Waters of Binuangeun, Banten - Suratno Suratno; Zahriza Purnadayanti; Hilda Novianty; Selvia Oktaviyani (Indonesian Journal of Chemistry, 2021)
The high level of fish consumption was the main factor in the vulnerability of Hg exposure to the human body. The preliminary information of the total mercury (THg) concentration of Indian scad (Decapterus russelli) and Torpedo scad (Megalaspis cordyla) from Binuangeun fish auction in Lebak, Banten, Indonesia, was presented in this research. The objective of this research was to understand the distribution of THg in each organ of D. russelli (muscle, gut tissues, gonad, and eggs) and M. cordyla (muscle, liver, and gut contents). The results showed that THg in all samples were below the National Regulation limit from the National Agency of Drug and Food in mg/kg ww. THg gonad from D. russelli was showed highly significant (P < 0.01) lower compare THg in muscle, gut tissues, and eggs. Pearson’s correlation from THg in each organ of D. russelli compare to total weight and total length showed that concentration of THg in gonad highly significantly (p < 0.01) correlated with total body weight (r2 = 0.97) and total length (r2 = 0.96). M. cordyla was showed no correlation of THg in muscle compare to total length and total weight. The present study showed that D. russelli could accumulate higher mercury compare to M. cordyla and need caution while consuming this fish.